Lecturer professionalism: Local problems with the help of teaching aids to make students understand Prim’s, Cruscal’s, and Djiksra’s algorithms - Harisman, Yulyanti; Dwina, Fitrani; Tasman, Fridgo (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
This study aims to design case-based learning with lesson study learning trajectory with the help of teaching aids to make students understand Prim’s, Cruscal’s, and Djiksra’s Algorithms. The validation study was selected because it is a suitable method for this research. The research subjects were 41 Mathematics Education Study Program Students at Universitas Negeri Padang. This research data were collected using Interview guidelines, journals, and observation sheets. Data analysis was carried out by transcribing interviews, reducing, presenting, and drawing conclusions from the data. A lesson study was chosen as an alternative to improve and reflect on the learning process. Moreover, two expert lecturers supervised the groups during the learning process. A proper design of case-based learning with lesson study learning trajectory with the help of teaching aids development process is obtained. Using a case-based learning method can make students understand Prim’s, Cruscal’s, and Djiksra’s Algorithms. This design can be used by the other lecturers to provide a learning process of Prim’s, Cruscal’s, and Djiksra’s Algorithms or other topics.